Biomimetic and Biohybrid Systems First International Conference, Living Machines 2012, Barcelona, Spain, July 9-12, 2012. Proceedings - Prescott, Tony J.; Lepora, Nathan F.; Mura, Anna.; Verschure, Paul F. M. J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the proceedings of the First International Conference on Biomimetic and Biohybrid Systems, Living Machines 2012, held in Barcelona, Spain, in July 2012. The 28 full papers and 33 extended abstracts presented in this volume were carefully reviewed and selected for inclusion in this book. The conference addresses themes related to the development of future real-world technologies which will depend strongly on our understanding and harnessing of the principles underlying living systems and the flow of communication signals between living and artificial systems.
Keywords: Computer science; Artificial intelligence; Computer vision; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Computation by Abstract Devices; Pattern Recognition; Information Systems Applications (incl. Internet).; Image Processing and Computer Vision; Control, Robotics, Mechatronics